Enhancing Light-Trapping Properties of Amorphous Si Thin-Film Solar Cells Containing High-Reflective Silver Conductors Fabricated Using a Nonvacuum Process - Jun-Chin Liu; Chen-Cheng Lin; Yu-Hung Chen; Chien-Liang Wu; Chia-Ming Fan; Yu-Ming Wang; Chung-Yuan Kung (International Journal of Photoenergy)
We proposed a low-cost and highly reflective liquid organic sheet silver conductor using back contact reflectors in amorphous silicon (a-Si) single junction superstrate configuration thin-film solar cells produced using a nonvacuum screen printing process. A comparison of silver conductor samples with vacuum-system-sputtered silver samples indicated that the short-circuit current density (Jsc) of sheet silver conductor cells was higher than 1.25 mA/cm2. Using external quantum efficiency measurements, the sheet silver conductor using back contact reflectors in cells was observed to effectively enhance the light-trapping ability in a long wavelength region (between 600 nm and 800 nm). Consequently, we achieved an optimal initial active area efficiency and module conversion efficiency of 9.02% and 6.55%, respectively, for the a-Si solar cells. The results indicated that the highly reflective sheet silver conductor back contact reflector layer prepared using a nonvacuum process is a suitable candidate for high-performance a-Si thin-film solar cells.